2001
DOI: 10.1074/jbc.m011754200
|View full text |Cite
|
Sign up to set email alerts
|

d-Aspartate Is Stored in Secretory Granules and Released through a Ca2+-dependent Pathway in a Subset of Rat Pheochromocytoma PC12 Cells

Abstract: (7). In the pineal gland, it has been shown that D-aspartate is present in pinealocytes, endocrine cells for melatonin (8,9). Upon incubation of pinealocytes with exogenous D-aspartate, melatonin synthesis is strongly inhibited through the inhibition of N-acetyltransferase activity (9, 10). Thus, D-aspartate seems to be a modulator of melatonin synthesis. Furthermore, exogenous Daspartate stimulates the release of luteinizing hormone and growth hormone in the anterior pituitary (11).As chemical transmitters, D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
31
2

Year Published

2002
2002
2017
2017

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 48 publications
(34 citation statements)
references
References 45 publications
1
31
2
Order By: Relevance
“…Recently, we showed that D-aspartate is accumulated in secretory granules and secreted from PC12 cells (48). Thus, co-secretion of excitatory amino acids with hormones might be a common feature in endocrine signal transmission.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, we showed that D-aspartate is accumulated in secretory granules and secreted from PC12 cells (48). Thus, co-secretion of excitatory amino acids with hormones might be a common feature in endocrine signal transmission.…”
Section: Discussionmentioning
confidence: 99%
“…5,10,11) In brief, cultured cells (1ϫ10 7 cells) were washed three times with a Ringer's solution comprising 10 mM HEPES, pH 7.4, 0.2% BSA, 4.7 mM KCl and 2. Ringer containing 50 mM KCl was used.…”
Section: Methodsmentioning
confidence: 99%
“…The antibodies did not cross react with L-aspartate or L-glutamate, or other related amino acids, the details being given previously. 11) Monoclonal antibodies against insulin were obtained from Cymbus Biotechnology Ltd.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations